Cyberslacking Behaviors in Healthcare Professionals - Kıymet Koç; Serap Altuntaş (Association of Nurse Managers, 2021)
Together with the use of the internet in working life, the communication activities of organizations and the services they provide have become more productive and faster. However, problems such as the use of the internet by employees for their special purposes outside work have also emerged. This condition is defined as cyberslacking behavior in the literature, which indicates personal use of the internet by employees outside their tasks in the workplace environment. Since the sensitivity and attention to be showed by medical personnel will directly affect human health when providing healthcare services, it is necessary to put emphasis on cyberslacking behavior of healthcare professionals, especially nurses who maintain the care of patients full time. Studies investigating cyberslacking behavior in health sector are not adequate in number. This study has compiled the results of studies giving information about cyberslacking behavior in healthcare professionals.